2019
DOI: 10.1016/j.rgmx.2018.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Detección de tumores neuroendocrinos pancreáticos: 23 años de experiencia

Abstract: Differences were observed between the previously published case series and the current results. There was an increase in incidentalomas and non-functioning tumors, but no variation in the overall survival rate. The differences with other case series (age, sex, and tumor location) were dependent on the country where the cases were compiled. The increase in tumors could be related to a higher number of diagnoses made through imaging studies and to the greater sensitivity of the devices employed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
2
0
2
Order By: Relevance
“…Se demostró que el manejo del tumor neuroendocrino tiene como componente principal el tratamiento quirúrgico, al observar nuestra experiencia con respecto al tratamiento postoperatorio optado, ya que sólo aquellos pacientes con nivel de resección quirúrgica R1 fueron beneficiarios de tratamiento complementario con quimioterapia y radioterapia [15][16].…”
Section: Discussionunclassified
“…Se demostró que el manejo del tumor neuroendocrino tiene como componente principal el tratamiento quirúrgico, al observar nuestra experiencia con respecto al tratamiento postoperatorio optado, ya que sólo aquellos pacientes con nivel de resección quirúrgica R1 fueron beneficiarios de tratamiento complementario con quimioterapia y radioterapia [15][16].…”
Section: Discussionunclassified
“…Neuroendocrine tumors represent a group of rare neoplasms, with an overall incidence of approximately 5.25/100000 [1]. The pancreatic neuroendocrine tumors (PNETs) represent only 1–2% of all pancreatic malignancy tumors, with incidence of 1–5 cases per million, mainly afflicting adults between the ages of 30 to 60 years; however, recent advances in imaging technologies and application of endoscopic ultrasound have led to an increase in the number of diagnosed PNETs [25]. Case reports in the literature have indicated that the most common sites of these tumors are the gastrointestinal tract, lung, adrenal gland, and thyroid gland [1, 6].…”
Section: Introductionmentioning
confidence: 99%
“…PNETs develop from the embryonic neural crest cells that later give rise to islet cell tissue and are classified as functioning or non-functioning depending on the presence of clinical manifestation secondary to the tumor cells’ increased hormonal secretion (i.e. insulin, gastrin vasoactive intestinal peptide, glucagon, and somatostatin) [3, 5, 6]. PNETs are also classified histologically as well differentiated, poorly differentiated, or mixed endocrine-exocrine subtypes [6].…”
Section: Introductionmentioning
confidence: 99%
“…Por otro lado, la tomografía computarizada (TC) permite la localización del tumor primario y de posibles lesiones secundarias, con una sensibilidad del 30 % para tumores de 1 a 3 cm, y un 95 % para los tumores >3 cm (14,16), con una notable mejoría de su rendimiento mediante el uso de técnicas multifásicas.…”
unclassified